Factors influencing the use of subcutaneous or transvenous implantable cardioverter-defibrillators: results of the European Heart Rhythm Association prospective survey. Issue 5 (8th February 2018) - Boveda, Serge; Lenarczyk, Radoslaw; Fumagalli, Stefano; Tilz, Roland; Gościńska-Bis, Kinga; Kempa, Maciej; Defaye, Pascal; Marquié, Christelle; Capucci, Alessandro; Ueberham, Laura; Dagres, Nikolaos
Abstract: The purpose of this European Heart Rhythm Association (EHRA) prospective snapshot survey is to provide an overview of the factors influencing patient selection for the implantation of a particular type of device: subcutaneous implantable cardioverter-defibrillator (S-ICD) or transvenous implantable cardioverter-defibrillator (TV-ICD), across a broad range of tertiary European centres. A specially designed electronic questionnaire was sent via the internet to tertiary reference centres routinely implanting both TV-ICDs and S-ICDs. These centres were asked to prospectively include and fill-in this questionnaire for all consecutive patients implanted with an implantable cardioverter-defibrillator (ICD) (both TV-ICD and S-ICD) during an 8-week period of time. Questions concerned standards of care and policies used for patient management, focusing particularly on the reasons for choosing one or the other type of ICD for each patient. In total 20 centres participated at the survey and entered individual data from a total of 429 consecutive patients (men 76.3%). Indication of implantation was primary prevention for 73% of the patients. Implanted devices were distributed between cardiac resynchronisation therapy (CRT) ones with back-up defibrillators (31.6%), single-chamber TV-ICD (29.5%), S-ICD (19.8%), and dual-chamber TV-ICD (19.1%).The rate of S-ICD shows the current penetration of this treatment in everyday practice. Main reasons favouring the use of an S-ICD were young age (66.7%), anticipated (38.9%) or previous (9.3%) lead-related complications, and elevated risk (18.5%) or previous device infection (7.4%). Importantly, the choice for this device was also based on patient preference (16.7%) or active lifestyle (13%). The three most frequent reasons for the use of a transvenous device were the option of antitachycardia pacing (43.2%), and logically, the current or expected need for CRT (40%) or for permanent pacing (39.6%). This snapshot survey with individual patient data provides a contemporary insight into ICD implantation and management in the European electrophysiology tertiary centres. It also helps to better understand the reasons which condition the choice between a S-ICD and a traditional TV-ICD. Finally, it gives a picture of the distribution of various types of ICD, few years after the introduction of the S-ICD in the Europe.